Type 2 Diabetic Patients and Their Awareness About Obstructive Sleep Apnea in Diabetic Centers of Riyadh City - Ahmed H. Mujamammi; Essa M. Sabi; Faisal M. Alsaawi; Naif A. Alfahed; Omar A. Alrajhi; Hamad A. Alshaalan; Mohamed F. Alqahtani; Mohammed A. Alamer (Wiley, 2024)
ABSTRACT Aims Lack of obstructive sleep apnea (OSA) awareness both directly and indirectly causes a medical and financial burden worldwide. The objective of this study is to provide new insights, focusing on type 2 diabetics and their knowledge levels about OSA in King Khalid University Hospital (KKUH), Riyadh, Saudi Arabia, and to recognize obesity as a common risk factor contributing to OSA in type 2 diabetes mellitus (T2DM) participants. Methods An analytical cross‐sectional study was conducted from July 2022 to December 2022 with a convenience sampling method of 386 participants (18 years old and above). The study was done face‐to‐face using an electronic questionnaire. The inclusion criterion was all T2DM patients at the waiting area of KKUH Diabetes Center in Riyadh, excluding participants with other metabolic disorders. Results Overall knowledge levels were poor, with 70.2% of participants not knowledgeable about the disease and 81.3% of participants having no knowledge concerning the bidirectional relationship between T2DM and OSA. Statistical significance was found between the risk of developing OSA symptoms and body mass index ≥30 (p ≤ 0.001). Conclusion The majority have very little to no knowledge regarding OSA and its bidirectional relationship with T2DM, indicating the need to put more effort into improving participant's awareness in this regard. Moreover, obesity should be considered as a common risk factor, recommending patients to practice healthier habits to minimize the risks and decrease mortality.